Contemporary Trends in International Economic Integration: Challenges and Prospects - Tukhliev, Nurislom; Abdullayev, Ravshan; Gulnora, Gulyamova; Batirova, Nilufar; Uktam, Jiyanov (International Journal of Psychosocial Rehabilitation, 2020)
In the second half of the 20th century, the system of international economic relations widely studied regional and international economic integration processes and their trade, capital and migration relations. However, as a result of disintegration processes in the system of international economic relations in the 21st century, disintegration processes in the European Union and North America have begun to be widely investigated. This article also examines the integration and disintegration processes in the global economy and highlights the urgency of the topic. The study analyzes the stages of EU integration and the causes that led to the disintegration, the peculiarities of the integration processes in North America, and their impact on the integration of Central Asian countries